How to train your dragon 1 & 2 [videorecording (DVD)] - Sanders, Chris (Christopher Michael); Sanders, Chris (Christopher Michael); Deblois, Dean; Deblois, Dean; Cowell, Cressida (Universal Pictures Home Entertainment, 2019)
Hiccup, a young Viking, aspires to become a dragon slayer but upon capturing a dragon he cannot kill it and befriends the dragon instead; Hiccup and Toothless must protect the peace when they find a cave that is home to hundreds of wild dragons.